Teaching approach of ACLS in cardiac arrest with pregnancy - Adel Hamed Elbaih; Anas Yahia Alkhalaileh; Ossama Ashour Haikal (Medicine Science, 2021)
Cardiac arrest is the abrupt loss of heart function in a person. Cardiac arrest can be lifesaving and it is important to understand the causes of maternal mortality to have an understanding of the unique pathogenic factors that may have precipitated the maternal cardiac arrest. Therefore, we aim to look into the common pitfalls that both medical students and new physicians face in the recognition, diagnosis, and management of these conditions. All Cardiac arrest pregnant patients who are requiring urgent management in the ED, with Emergency Physicians for teaching approach protocol. Appropriate for assessment and priorities for Cardiac arrest pregnant patients by training protocol to Emergency Physicians. Based on patients causes of Cardiac arrest pregnant women. Collection of all possible available data about the Pregnancy with cardiac arrest in the Emergency department. By many research questions to achieve these aims so a midline literature search was performed with the keywords critical care, emergency medicine, principals of resuscitation in Pregnancy ", "ACLS with cardiac arrest in pregnancy. Literature search included an overview of recent definition, causes and recent therapeutic strategies. All studies introduced that the initial diagnosis of Pregnancy with cardiac arrest and their therapy is a serious condition that face patients of the emergency and critical care departments. Maternal cardiac arrest is a complex clinical scenario, and the resuscitation of the pregnant woman involves multi-specialties and complex care decisions. This review is hopefully enough to strengthen the knowledge of new physicians and, hopefully with the recommendations, reduce the rates of false diagnoses. [Med-Science 2021; 10(3.000): 1075-80]